Rapid evidence review: Policy actions for the integration of public health and health care in the United States - Lin, Jennifer S.; Webber, Elizabeth M.; Bean, Sarah I.; Martin, Allea M.; Davies, Melinda C. (Frontiers in Public Health, 2023)
Objective To identify policy actions that may improve the interface of public health and health care in the United States. Methods A rapid review of publicly-available documents informing the integration of public health and health care, and case examples reporting objective measures of success, with abstraction of policy actions, related considerations, and outcomes. Results Across 109 documents, there were a number of recurrent themes related to policy actions and considerations to facilitate integration during peace time and during public health emergencies. The themes could be grouped into the need for adequate and dedicated funding; mandates and shared governance for integration; joint leadership that has the authority/ability to mobilize shared assets; adequately staffed and skilled workforces in both sectors with mutual awareness of shared functions; shared health information systems with modernized data and IT capabilities for both data collection and dissemination of information; engagement with multiple stakeholders in the community to be maximally inclusive; and robust communication strategies and training across partners and with the public. Conclusion While the evidence does not support a hierarchy of policies on strengthening the interface of public health and health care, recurrent policy themes can inform where to focus efforts.